FOMC communication policy and the accuracy of fed funds futures - Menno Middeldorp (Federal Reserve Bank of New York, 2011)
Over the last two decades, the Federal Open Market Committee (FOMC), the rate-setting body of the United States Federal Reserve System, has become increasingly communicative and transparent. According to policymakers, one of the goals of this shift has been to improve monetary policy predictability. Previous academic research has found that the FOMC has indeed become more predictable. Here, I contribute to the literature in two ways. First, instead of simply looking at predictability before and after the Fed's communication reforms in the 1990s, I identify three distinct periods of reform and measure their separate contributions. Second, I correct the interest rate forecasts embedded in fed funds futures contracts for risk premiums, in order to obtain a less biased measure of predictability. My results suggest that the communication reforms of the early 1990s and the guidance provided from 2003 significantly improved predictability, while the release of the FOMC's policy bias in 1999 had no measurable impact. Finally, I find that FOMC speeches and testimonies significantly lower short-term forecasting errors.
Keywords: D83; E58; G13; G14; 330; central bank communication; central bank transparency; futures pricing; financial market efficiency